Culture and international law : proceedings of the International Conference of the Centre for International Law Studies (CILS 2018), October 2-3, 2018, Malang, Indonesia - Juwana, Hikmahanto, 1965-; Thomas, Jeffrey E., 1959-; Rusli, Mohd Hazmi Mohd; Puspitawati, Dhiana (Boca Raton : CRC Press LLC, 2019)
In this era of globalization, International Law plays a significant role in facing rapid development of various legal issues. Cultural preservation has emerged as an important legal issue that should be considered by States. This book consists of academic papers presented and discussed during the 9th International Conference of the Centre of International Law Studies (9th CILS Conference) held in Malang, Indonesia, 2-3 October 2018. The title of the book represents the major theme of the conference: "Culture and International Law." It is argued that along with globalization, cultural preservation is slowly ignored by States. Various papers presented in the book cover five topics: cultural heritage; cultural rights; culture and economic activity; culture and armed conflict; and a general topic. The authors of thepapers are outstanding academics from various countries, Lithuania, United States of America, Australia, Thailand and Indonesia.The conference was organized by Universitas Indonesia in collaboration with Brawijaya University. This book aims to give a useful contribution to the existing literature on International Law, specifically focussing on cultural issues from the perspective of cultural heritage and rights, economic as well as armed conflict.
Description based upon print version of record.
OCLC-licensed vendor bibliographic record.
Keywords: TECHNOLOGY / Engineering / Civil; TECHNOLOGY / Engineering / Industrial; LAW / Criminal Law / General; Culture and law; International law